From The Front de gauche to La France insoumise: Causes and Consequences of the Conversion of the French Radical Left to Populism - Alexandre, Chloé; Bristielle, Antoine; Chazel, Laura (PARTECIPAZIONE E CONFLITTO, 2021)
Combining a variety of materials and a mixed methods approach, this article shows how the space of the French radical left has evolved since the 2000s. It outlines the transition from a Marxist to a post-Marxist ideology, and the creation of two new organizations - the Front de gauche (Left Front), which aimed to bring together the radical left, and La France insoumise (Unbowed France), which sought to federate the people using a more transversal populist strategy. The similarities and differences between the two strategies are put into perspective, from a discursive point of view and at the level of the electorate.